Can increased educational attainment explain declining Indigenous fertility?. Issue 3 (26th November 2019) - Venn, Danielle; Dinku, Yonatan
Abstract: Prior research shows that Aboriginal and Torres Strait Islander women are more likely to have children and have more children, on average, than non‐Indigenous women. However, like those of the total Australian population, fertility rates of Indigenous women have been declining since the 1970s. The decline has been more significant in recent years. Between 2006 and 2016, an increasing proportion of Indigenous women postponed childbirth from their teens into their 20s and 30s, leading women to have fewer children over their lifetimes. During the same period, there was a rapid increase in educational attainment among the Indigenous population. This paper examines educational gradients in fertility among Indigenous women and whether the observed fertility decline is linked with the increased educational attainment. Using data from the 2006, 2011 and 2016 Australian Census of Population and Housing and applying a shift‐share decomposition analysis, we find that education has been a big driver of falling fertility rates in non‐remote areas. In remote areas, education has had a much smaller effect (except for youngest women).